Crystal sheet lattices: Novel mechanical metamaterials with smooth profiles, reduced anisotropy, and enhanced mechanical performances - Qingyuan Liu; Yang Zhou; Zhenjie Zhang; Jinguo Ge; Shuai Yuan; Yuhong Long; Liao Zhou; Tielin Shi (Materials & Design, 2022)
Cellular materials with smooth profiles, improved structural strength, and reduced elastic-anisotropy are eternal pursuit in bone-implant filed. However, it is a huge task to meet so many requirements. In this work, a novel class of mechanical metamaterials, named as crystal sheet lattices, were proposed. The elastic performances were investigated using representative elementary volume model and examined by quasi-static compression tests. The plastic performances and energy absorption behaviors were experimentally calibrated. Meanwhile, elastoplastic simulations were adopted to study the deformation mode on the structural strengthen mechanism. The results demonstrate that the reduced elastic-anisotropy can be achieved without complicated regulation process. Under the same material volume fraction, the stiffness, yield strength, and energy absorption capability were respectively increased about 30%–60%, 30%–150%, and 70%–280%, for most of crystal sheet lattices in comparison with their truss-based counterparts. Being open type cellular materials, the crystal sheet lattices are of high mass-specific mechanical performances. Due to the smooth profiles, large surface volume ratios, and enhanced mechanical performances, CSLs also have potentials to be utilized in lightweight and heat transportation fields.